Origin of dogs entered Peru during the period 2009-2018 and potential risk of introduction of exotic zoonotic agents - Levaggi, Valeria (2022)
The aim of this study was to determine the origin of dogs admitted to Peru during the period 2009-2018 and to evaluate the potential risk of introduction of exotic zoonotic agents. The records of the National Agrarian Health Service (SENASA) of the entry of dogs into Peru in the indicated period were used. Complete information was obtained from 40 860 dogs. The results show a growing trend of annual entering of dogs to Peru, from 2273 in 2009 to 6382 in 2018, with higher frequencies in the months of December (16.2%), January (9.4%) and July (8.5%). The origins of the dogs were mainly from South America (44.3%), North America (29.4%) and Europe (17.4%), specifically from the United States (27.5%), Chile (13.4%), Argentina (11.4%) and Spain (8.8%). The main gateway was Lima International Airport (46.5%) and the and the Aero Port Control Office of the airport for dogs that entered as cargo (45.6%). The study offers information on exotic zoonotic diseases for Peru, but exotic and endemic with reservoir in dogs in the countries of origin of dogs interned in Peru